Effect of rootstock and boron and zinc on the vegetative growth characteristics of Mediterranean tangerine trees Mediterranean mandarin (Citrus deliciosa Tenore) - جعفر, رائد; علي ديب ,; علي الخطيب, (Latakia University Journal -Biological Sciences Series, 2025)
This study was conducted during the year 2023 on Mediterranean tangerine trees (Mandarin tangerine), grown at the syano Research Station of the General Authority for Scientific Agricultural Research (Lattakia Research Center), with the aim of studying The effect of the rootstock and foliar spraying with boron and zinc on the vegetative growth characteristics of the trees of the studied species. The study included three rootstocks, Troyer citrange, Citrumelo 4475, and trifoliate orange (Poncirus trifoliata. (L). Raf), and spraying with the Boron element at a concentration of 200 ppm, and zinc element at a concentration of 100 ppm, singly and mixed. The results showed that the largest increase in crown size was at the Troyer Citrange rootstock, followed by the Citromilo 4475 rootstock, then (Poncirus trifoliata. (L). Raf) rootstock. As the results show, for the rest of the indicators (average length of shoots, average number of leaves, average leaf area), the spraying treatment with boron and zinc mixed was superior (200+100)ppm, followed by the zinc treatment alone at a concentration of 100ppm, then the boron treatment at a concentration of 200ppm, and all treatments was superior on the control treatment. As for the mutual influence between the rootstock and foliar spraying factors, the spraying treatment with boron and zinc mixed on the Troyer citrang rootstock was also The highest value was superior to the rest of the treatments and rootstocks, followed by the treatment of spraying with zinc alone and on the same rootstock, Troyer citrang, with a significant difference over the rest of the treatments. It is also clear that the lowest average values were for the treatments applied to (Poncirus trifoliata. (L). Raf) rootstock, and the control treatment on all the rootstocks.